The meanings of university social commitment. An approach towards constructing the state of the art - Gerlero, Carina Andrea (2016)
Fil: fill.Gerlero, Carina Andrea. Universidad Nacional de Rosario. Ministerio de Educación, Santa Fe; Argentina.